Enhancing the open-circuit voltage of perovskite solar cells by up to 120 mv using π-extended phosphoniumfluorene electrolytes as hole blocking layers - An, Qingzhi; Sun, Qing; Weu, Andreas; Becker-Koch, David; Paulus, Fabian; Arndt, Sebastian; Stuck, Fabian; Hashmi, A. Stephen K.; Vaynzof, Yana (Advanced energy materials, 2019)
Four π-extended phosphoniumfluorene electrolytes (π-PFEs) are introduced as hole-blocking layers (HBL) in inverted architecture planar perovskite solar cells with the structure of ITO/PEDOT:PSS/MAPbI3/PCBM/HBL/Ag. The deep-lying highest occupied molecular orbital energy level of the π-PFEs effectively blocks holes, decreasing contact recombination. It is demonstrated that the incorporation of π-PFEs introduces a dipole moment at the PCBM/Ag interface, resulting in significant enhancement of the built-in potential of the device. This enhancement results in an increase in the open-circuit voltage of the device by up to 120 mV, when compared to the commonly used bathocuproine HBL. The results are confirmed both experimentally and by numerical simulation. This work demonstrates that interfacial engineering of the transport layer/contact interface by small molecule electrolytes is a promising route to suppress nonradiative recombination in perovskite devices and compensates for a nonideal energetic alignment at the hole-transport layer/perovskite interface.